Industrial development in Nigeria : patterns, problems, and prospects - Teriba, O.; Kayode, M. O. (Ibadan, Nigeria : Ibadan University Press, 1977)
This book seeks to focus on economic transformation in the country in order to interest both policy-makers and general readers. It contains 28 contributions, 8 of which have been published previously, mainly in the Nigerian Journal of Economic and Social Studies (Ibadan). These include among others the famous study of 'Planning for Further Industrial Development in Nigeria' by P. C. Asiodu, Asiodu, and 'Towards a New Industrial Location Policy' by O. Aboyade.
Includes index.
Bibliography: p. 389-393.
lje 17/1/18
Loans
Keywords: Industrialization; Industrial policy; Industrial promotion